Parametric BIM façade module development for diagrid twisted structures - Akkoyunlu, Tahir (International Association for Automation and Robotics in Construction I.A.A.R.C), 2018)
Building Information Modelling (BIM) is an epochal phenomenon in AEC. Most of the developed countries has already adopted BIM by regulations. Biggest projects around the world executing by BIM which provides more effective project management process. Whole construction progress including; feasibility, design, construction and commissioning became digital visualization. Any required analysis can be done via this model template. In fact, requesting the complex and sophisticated structures’ construction is the main catalyst of developing BIM. Mankind start to design and construct cutting-edges and pushing limit structures. Twisted towers are one of the significant instance of like these structures. This study embrace the twisted towers’ façade design which has one of the most complex patterns. So it is thought that if such these towers’ façade system can be organized and customized limitlessly, most of the façades systems will be solved for the optimum result. This study aims to reveal a method which can be used for to develop easily alternative façade systems for construction projects even they have very complex design. One of the most complex structures the twisted diagrid systems which are constructed currently around the world was selected. BIM and computational programming have been used to improve the module.
Keywords: BIM; Building Information Modelling; Computational BIM; Parametric Design; Twisted Towers; Visual Programming